Subdifferential Frictional Contact Problem with Thermo-Electro-Visco-Elastic Locking Materials: Analysis and Approximation (Journal of Nonlinear Modeling and Analysis, 2025)
This paper investigates a frictional contact problem involving athermo-electro-visco-elastic model for locking materials in contact with a rigidfoundation. Friction is described by the subgradient of a locally Lipschitzfunction, while contact is governed by Signorini’s unilateral condition. Weformulate the problem as a system of three hemivariational inequalities andestablish an existence and uniqueness theorem using a fixed-point argumentand recent advances in hemivariational inequalities theory. Finally, we presenta fully discrete finite element approximation of the model and derive errorestimates for the approximate solution.